Structure formation of hypereutectic Al-Si-alloys produced by laser surface treatment - Grigoriev, Sergey N. (Strojniški vestnik, 2014)
Using a coaxial laser cladding process AlSix (X=30, 40, 60) clad tracks were produced. The mechanisms of structure formation in Al-Si alloys during laser cladding were studied. Particle size distribution, surface morphology and microstructure of the initial powders were investigated. The influence of the chemical composition of the powder material on the structure and the microhardness of the coating has been shown, as well as the influence of processing parameters on the microstructure and the geometry of the resulting tracks. Conclusions about the technological possibility of manufacturing single tracks with widths of < 500 um based on an Al metallic matrix bearing a Si content ranging from 30 to 60 wt.% Si have been made.
Keywords: aluminijeve zlitine; aluminium alloy; lasersko navarjanje; materiali majhne gostote; mikronavarjanje; mikrostruktura; oblikovanje navarjene sledi; oblikovanje strukture